Does an Early Speech Preference Predict Linguistic and Social-Pragmatic Attention in Infants Displaying and Not Displaying Later ASD Symptoms? - Yamashiro, Amy; Curtin, Suzanne; Vouloumanos, Athena (Journal of Autism & Developmental Disorders, 2020)
Human infants show a robust preference for speech over many other sounds, helping them learn language and interact with others. Lacking a preference for speech may underlie some language and social-pragmatic difficulties in children with ASD. But, it's unclear how an early speech preference supports later language and social-pragmatic abilities. We show that across infants displaying and not displaying later ASD symptoms, a greater speech preference at 9 months is related to increased attention to a person when they speak at 12 months, and better expressive language at 24 months, but is not related to later social-pragmatic attention or outcomes. Understanding how an early speech preference supports language outcomes could inform targeted and individualized interventions for children with ASD.